OPEN PRACTICE-ORIENTED TASKS AS A TOOL FOR THE DEVELOPMENT OF INFORMATION LITERACY OF PRIMARY SCHOOL CHILDREN - Sergeeva, Larisa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the actual problem of organizing the educational process aimed at developing information literacy in schoolchildren when studying mathematics at one of the most difficult stages of learning - at the stage of transition from primary to basic school. This paper describes some areas of information literacy development in primary school students; the analysis of the main groups of actions, with the help of which the ability of younger students to work with mathematical information can be formed; describes the results of the performance by younger students of a set of tasks aimed at the formation of information literacy based on the work of students with open practice-oriented tasks. The empirical experience of using the proposed methodology and the analysis of the results obtained made it possible to obtain data on the level of mastery of information literacy by younger students.